ANALISIS PENGARUH PENERAPAN CORPORATE SOCIAL RESPONSIBILITY(DIVERSITY & EMPLOYEE SUPPORT) TERHADAP KINERJA KARYAWAN (STUDI KASUS PT. BATU RONA ADIMULYA) - TITIN HERYANI; ZUNAIDAH . (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2013)
The purpose of this research are: (1). Analyzing the concept influence of Diversity and Employee partially support against the performance of PT.Baturona Adimulya employee. (2). Analyzing the concept influence of Diversity and Employee support simultaneous against the performance of PT Baturona Adimulya employee (3). Knowing which variable that have a dominant influence against the performance of PT. Baturona Adimulya employee. The result of the first hypothesis test showed diversity only influence of 0.089. So diversity variable partially doesn't have a significant influence against the performance of PT. Baturona Adimulya employees. Further variable emlpoyee support influence at 0.896 and significant means employee support partially has a significant influence against the performance of PT. Baturona adimulya employee. Further the second hypothesis testing showed a value of 0.658 (coefficient of determination). These results state diversity and employee support simultaneously (together) have a significant influence against the performance of PT. Baturona Adimulya employees. The results of the employee support third variables influence more dominant when compared with diversity variable against the performance of PT. Baturona Adimulya employees.